Positioning and Categorizing Mass Media Using Reaction Emojis on Facebook. (26th December 2020) - Wang, Ming-Hung
Abstract: With the rapid growth of social network services, a paradigm shift in communication between media organizations and the audience has occurred. Numerous mass media agencies established fan pages on social platforms, such as Facebook, Twitter and Instagram, to disseminate breaking news, promote reports and interact with their audience. In this study, we leverage the reaction emojis delivered from users to media fan pages on Facebook to investigate how users react to media organizations and the implications of selective exposure. Using a 1-year-long observation of user activities on mass media pages, we perform a series of quantitative approaches to locate media agencies, measure the distances between them and cluster organizations into groups. A total of 30 fan pages of mass media organizations in Taiwan are investigated. The outcomes suggest that the report genres and topics are key factors to categorize media groups through reaction emojis from the online audience.